2017
DOI: 10.1002/hep.28944
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric acute liver failure of undetermined cause: A research workshop

Abstract: Pediatric Acute liver failure (PALF) is a potentially devastating condition which occurs in previously healthy children of all ages and frequently leads to a rapid clinical deterioration. An identified cause for liver injury is lacking in approximately 30% of cases. Children with undetermined diagnosis have lower spontaneous survival and higher rates of transplantation and death than other diagnostic groups. A single day workshop sponsored by the National Institute of Diabetes and Digestive and Kidney Diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 48 publications
3
78
1
1
Order By: Relevance
“…Patients in this group, called indeterminate PALF (iPALF), have worse outcomes and are more likely to undergo liver transplantation (LT) than those with known diagnosis (dPALF) . To date, little is known about the pathophysiology of iPALF, but growing evidence supports the hypothesis that the liver injury is immune‐mediated, resulting from an imbalance between proinflammatory and anti‐inflammatory factors . iPALF patients frequently exhibit signs of immune activation and dysregulation including cytopenias, elevated soluble interleukin‐2 receptor levels, natural killer cell dysfunction, and development of aplastic anemia (AA) either shortly before or after their liver injury.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Patients in this group, called indeterminate PALF (iPALF), have worse outcomes and are more likely to undergo liver transplantation (LT) than those with known diagnosis (dPALF) . To date, little is known about the pathophysiology of iPALF, but growing evidence supports the hypothesis that the liver injury is immune‐mediated, resulting from an imbalance between proinflammatory and anti‐inflammatory factors . iPALF patients frequently exhibit signs of immune activation and dysregulation including cytopenias, elevated soluble interleukin‐2 receptor levels, natural killer cell dysfunction, and development of aplastic anemia (AA) either shortly before or after their liver injury.…”
mentioning
confidence: 96%
“…(2,5) To date, little is known about the pathophysiology of iPALF, but growing evidence supports the hypothesis that the liver injury is immune-mediated, resulting from an imbalance between proinflammatory and anti-inflammatory factors. (6)(7)(8)(9)(10)(11) iPALF patients frequently exhibit signs of immune activation and dysregulation including cytopenias, elevated soluble interleukin-2 receptor levels, natural killer cell dysfunction, and development of aplastic anemia (AA) either shortly before or after their liver injury. It is now accepted that immune dysregulation plays a key role in propagating liver injury in the majority of iPALF cases.…”
mentioning
confidence: 99%
“…Recent studies have suggested that patients with ALF have an immune dysregulation pattern similar to observations in HLH[ 11 , 19 ]. Some patients with ALF present with elevated ferritin and sIL-2R levels, low fibrinogen, and numerous infiltrating CD8+ T cells on liver biopsy, which are compatible with those found in HLH[ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 86%
“…Indeterminate ALF necessitates a broad evaluation for underlying etiologies; both infectious and noninfectious are included. Although screening for common forms of viral hepatitis, including hepatitis A to E is nearly universal, testing for viruses less frequently considered hepatropic may not always be complete[ 10 , 11 ]. For example, some cases of herpes virus-associated fulminant hepatitis were only confirmed by postmortem liver biopsy[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute liver failure (ALF) and secondary HLH Some cases of acute liver failure are associated with HLH. The condition has been described in both adults and children (Giard et al 2016;Lin et al 2016;Alonso et al 2017). The presence of rampant immune activation and dysregulation with associated ALF makes the diagnosis of HLH difficult.…”
Section: Macrophage Activation Syndrome (Mas)mentioning
confidence: 99%